2018
DOI: 10.1515/humo-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-examiner reliability in angular measurements of the knee with a smartphone application

Abstract: Purpose. Goniometric smartphone applications to measure joint angles offer greater practicality and accessibility, which makes them potential alternatives to a conventional goniometer. The aim of the present study was to evaluate the intra-and interexaminer reliability in measuring the angles of the range of motion of the knee with the use of the ROM© goniometric smartphone application. Method. The total of 34 young healthy women with an at least 20° limitation in knee extension range of motion participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
1
Order By: Relevance
“…Moreover, the current study demonstrated a higher ICC value than that reported by Derhon et al (2017), who showed a good intra-tester correlation (ICC > 0.85) of passive knee flexion ROM in healthy women. The SEM and MDD values in the present study seemed to be extremely similar to those of Mehta et al (2017), who reported smaller SEM (2.72°) and MDD (6.3°) in assessing knee flexion ROM.…”
Section: Discussioncontrasting
confidence: 66%
“…Moreover, the current study demonstrated a higher ICC value than that reported by Derhon et al (2017), who showed a good intra-tester correlation (ICC > 0.85) of passive knee flexion ROM in healthy women. The SEM and MDD values in the present study seemed to be extremely similar to those of Mehta et al (2017), who reported smaller SEM (2.72°) and MDD (6.3°) in assessing knee flexion ROM.…”
Section: Discussioncontrasting
confidence: 66%
“…currently, smartphones, in addition to their function as cell phones, are pocketsized minicomputers with an extremely large number of applications and count less sensors such as accelerometers, global position ing systems, and travel speed detectors. smartphones have facilitated accessibility for the measurement of several physiological and biomechanical variables such as movement speed [9], jump height [10,11], HR [12], blood pressure, and blood glucose [13]. Because of advancements in technology, the variety of applica tions available on digital platforms have increased the use of smartphones, allowing the measurement of physiological variables such as HR monitoring at rest and during physical exercise [5,14].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on the validity and reliability of smartphone applications for joint angle measurement; 37 articles were included in a systematic review by Keogh et al 14) Nine of these papers obtained knee joint angle measurements 6,15,[17][18][19][20][21][22][23] using six applications that were used as accelerometers, which were all evaluated for validity and reliability. Of these applications, two were used on a Samsung Galaxy 21,22) device, while the other four were used on an Apple iPhone 6,15,[17][18][19][20]23) . However, unlike the accelerometer app, the photo-based app is intuitive and easy to use as it determines the angle of the basic axis as well as the measurement using a UG.…”
Section: Discussionmentioning
confidence: 99%